Simulation of The Application of an Adaptive Smart Envelope to an Existing Building in Rhinoceros Grasshopper - Rawi, Lina Qassim Al; Wahhab, Khalid Abdul (Al-Nahrain Journal for Engineering Sciences, 2022)
In recent decades, many factors have emerged in the building design field, as the technology development after the industrial revolution has left many environmental problems affecting building environments and turning them into unhealthy ones. Also, the issues of consuming natural resources required innovative and modern solutions to address, which needed the guidance and focus of researchers, engineers, and many other relevant disciplines to find the best treatments to solve them. One of the essential treatments was using advanced smart technology to solve the environmental problems of buildings, such as providing thermal comfort and reducing energy consumption. The concept of adaptive smart envelopes is one of this manifestation of advanced technology in the field of building design characterized by interaction and adaptation to the surrounding environment through the application of many technologies which it works to improve its environmental efficiency. The research aim was to simulate the changes in the building environment, which is treated by covering the building with an adaptive smart envelope by using the Rhinoceros Grasshopper programme.